The impact of urban-based family medicine postgraduate rotations on rural preceptors/teachers - Myhre, Douglas; Ornstein, Jodie; Whalen-Browne, Molly; Malhi, Rebecca L. (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2021)
Background: The use of rural rotations within urban-based postgraduate programs is the predominant response of medical education to the health needs of underserved rural populations.  The broader impact on rural physicians who teach has not been reported.Methods: This study examined the personal, professional, and financial impact of a rural rotations for urban-based family medicine (UBFM) residents on Canadian rural teaching physicians. A survey was created and reviewed by community and academic rural physicians and a cohort of Canadian rural family physicians teaching UBFM residents was sampled. Survey data and free-text responses were assessed using quantitative and qualitative analyses.  Results: Participants with rural residency backgrounds perceived a negative impact of teaching UBFM (p = 0.02 personal and professional) and those in a primary rural environment (as defined below) perceived impact as positive (p < 0.001). Rural preceptors often held contrasting attitudes towards learners with negative judgements counter-balanced by positive thoughts. Duration in practice and of teaching experience did not have a significant impact on ratings.Conclusion: Being a rural preceptor of UBFM residents is rewarding but also stressful. The preceptor location of training and scope of practice appears to influence the impact of UBFM residents.